LAC-UFF STATUS REPORT: CURRENT PROTOCOLS AND RECENT DEVELOPMENTS. Issue 4 (29th August 2021) - Oliveira, Fabiana; Macario, Kita; Carvalho, Carla; Moreira, Vinicius; Alves, Eduardo Q; Chanca, Ingrid; Diaz, Maikel; Jou, Renata; Hammerschlag, Izabela; Netto, Bruna M; Oliveira, Maria Isabela; Assumpção, Ayrton; et al.
ABSTRACT: The Radiocarbon Laboratory of the Fluminense Federal University was installed in 2009, and its NEC Single Stage Accelerator Mass Spectrometry system has been operational since 2012. As the first 14 C-AMS facility in Latin America, the LAC-UFF became a reference center for radiocarbon ( 14 C) dating in Brazil. Over the years we have implemented pretreatment protocols for several kinds of materials, such as cellulose, soil, bone, and biofuels. In the present paper we describe our current protocols for the preparation of these types of samples. Moreover, after 10 years of operation, with the aim of expanding the range of materials we are able to analyze, we report the results of several tests to improve accuracy, precision and background levels. For example, here we discuss how isotopic fractionation during the graphitization and measurement steps has been controlled. Concerning results interpretation, our research group has been using OxCal chronological models to analyze different contexts such as stromatolite growth, tree rings, soil deposition and marine reservoir effect (MRE) determination.